Maverick : a biography of Thomas Sowell - Riley, Jason L 1971- (Basic Books, 2021)
"In Maverick, Jason Riley explores the life and ideas of Thomas Sowell, one of America's most influential and trenchant Black social critics and conservative intellectuals alive today. Riley offers an introduction to Sowell's ideas, from race and inequality to politics, economics, and education. Riley considers Sowell's own history alongside the moments and movements that shaped his thinking"--